Clinical utility of a glycosylated fibronectin test (LumellaTM) for assessment of impending preeclampsia - Di Renzo, Gian Carlo; Arduini, Maurizio; Bartha, Jose Luis; Froeliger, Alizee; Jorgensen, Jan Stener; Kacerovsky, Marian; Stanirowski, Pawel; Wielgos, Miroslaw; Gao, Lina; Gravett, Michael G (Journal of maternal-fetal & neonatal medicine, 2025)
OBJECTIVE: Preeclampsia is a major pregnancy complication that results in significant maternal and infant mortality and morbidity, yet difficulties remain in the diagnosis of preeclampsia based on clinical parameters alone. The objective was to assess the performance of a hand-held point-of-care (POC) immunoassay in a clinical environment for glycosylated fibronectin (GlyFn) for the prediction of preeclampsia within 4 weeks of sampling. METHODS: Multinational European prospective observational pilot study of predominantly high-risk patients in the second half of pregnancy to assess a point-of-care immunoassay for GlyFn in predicting preeclampsia within 4 weeks of sampling. GlyFn was measured using a second generation hand held POC immunoassay. Results were considered normal for GlyFn concentrations of < 350 μg/mL, positive for GlyFn concentrations of 351-600 μg/mL, and high-positive for GlyFn concentrations > 600 μg/mL. RESULTS: Preeclampsia developed in 16 (19%) of 84 subjects and was associated with a shorter gestational age at delivery 35.3 weeks vs. 37.3 weeks for non-preeclamptics, n = 82; p = 0.001), a higher risk of fetal growth restriction (FGR; 31.2% vs. 10.3% for non-preeclamptics, p = 0.046), and an increased risk of preterm birth < 37 weeks gestation (83.3% vs. 33.3% for non-preeclamptics, (n = 78; p = 0.003). GlyFn positive or high positive was seen in 13/16 (81%) and in 35/68 (51.5%), yielding a sensitivity of 81%, a specificity of 49%, a positive predictive value of 27%, and a negative predictive value of 92%. GlyFn positive or high positive was also associated with preterm birth < 37 weeks in singleton pregnancy non-preeclamptic patients. Preterm birth occurred in 4.8% of those with normal GlyFn, in 26.7% with positive GlyFn, and in 50% of those with high GlyFn in singleton gestations without preeclampsia (p = 0.008). CONCLUSION: The ability to use this test in a POC format provides a method for practitioners to quickly determine risk for preeclampsia in their pregnant patients and offers an affordable alternative, as a single analyte to other diagnostic or screening tests that require laboratory-based testing or ultrasound equipment. Independent of preeclampsia, an elevated GlyFn was also correlated with preterm delivery and requires further study.
Keywords: imunoanalýza; těhotenství; Immunoassay; Point-of-Care Testing; Predictive Value of Tests; glykované proteiny; fibronektiny; Gestational Age; prediktivní hodnota testů; Glycated Proteins; Prospective Studies; Adult; vyšetření u lůžka; gestační stáří; ženské pohlaví; Fibronectins; Humans; prospektivní studie; Pregnancy; biologické markery; pilotní projekty; Pilot Projects; dospělí; Biomarkers; Female; point of care testing; Pre-Eclampsia; preeklampsie; lidé; Point-of-Care Systems